Anterior/posterior competitive deactivation/activation dichotomy in the human hippocampus as revealed by a 3D navigation task. - Isabel Catarina Duarte (Public Library of Science (PLoS), 2014)
Anterior/posterior long axis specialization is thought to underlie the organization of the hippocampus. However it remains unclear whether antagonistic mechanisms differentially modulate processing of spatial information within the hippocampus. We used fMRI and a virtual reality 3D paradigm to study encoding and retrieval of spatial memory during active visuospatial navigation, requiring positional encoding and retrieval of object landmarks during the path. Both encoding and retrieval elicited BOLD activation of the posterior most portion of hippocampus, while concurrent deactivations (recently shown to reflect decreases in neural responses) were found in the most anterior regions. Encoding elicited stronger activity in the posterior right than the left hippocampus. The former structure also showed significantly stronger activity for allocentric vs. egocentric processing during retrieval. The anterior vs. posterior pattern mimics, from a functional point, although at much distinct temporal scales, the previous anatomical findings in London taxi drivers, whereby posterior enlargement was found at the cost of an anterior decrease, and the mirror symmetric findings observed in blind people, in whom the right anterior hippocampus was found to be larger, at the cost of a smaller posterior hippocampus, as compared with sighted people. In sum, we found a functional dichotomy whereby the anterior/posterior hippocampus shows antagonistic processing patterns for spatial encoding and retrieval of 3D spatial information. To our knowledge, this is the first study reporting such a dynamical pattern in a functional study, which suggests that differential modulation of neural responses within the human hippocampus reflects distinct roles in spatial memory processing.